Sustainable relationships volume traffic towards noise inside motorcycle and non-motorcycles in the city Bogor - Syaiful, Syaiful; Mulyadi, Asep (International Journal of Engineering and Technology, 2019)
Motorcycles on the highway produce very varied noise. Noise also has a considerable impact on tranquility and comfort in areas directly in contact with roads. This research examines school SDN I Cibuluh No. 222, Bogor. The work steps are to measure the distance of the school area by the highway, take the traffic data and measure the noise level. The methods are (1) literature review, (2) initial survey, (3) data collection stage, (4) primary and secondary data processing, (5) analyzing data, and (6) drawing conclusions. The result of calculation shows that the relation of volume of motorcycle (x1) to noise (y) is 17,8% and the non motorcycle volume (x2) with noise is 3,8%. The conclusion obtained is that based on existing regulations for schools the allowable data of 55 dBA means that it is above the permissible threshold. The continuity of the vehicle volume relation with noise is very significant.Â Â